Education on physical and psychological changes in the elderly by increasing knowledge among cadres - Dwi Febriati, Listia (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2024)
Abstract Based on 1998 UUD #13 Continue Age is a person turning 60 years old. The proportion of older people doubled from 1971 to 2020, to 9.92% (about 26 million people), with 10.43% compared to 9.42% overall, with 1% more older women than men. This year, there are already six provinces with demographics that have already reached 10% of the elderly population, one of which is: DI Yogyakarta (14.71%) (Badan Pusat Statistik, 2020). Padukuhan Duku is located in Jambidan Sub-district Bangantapan Regency Bantul Village, DI Yogyakarta. It consists of four villages and two dwellings. For Padukuhan Duku villages, there are Genengan Village, Dhuku Village, Jambidan South Village and Jambidan Lor Village. Hamlet of Duku doing Covid-19 pandemic activity. This includes an integrated care center for the elderly. This has a huge impact on his one mental state alone. Activities carried out in the form of executive training for seniors. He sees it as a good fit to enable expanded capacity for cadres who attend to the elderly. The methods used in this activity are his advice for executive methods on the theory, physique and psychology of the elderly. We had a preliminary exam before the consultation team and had an activity consultation. Next Q&A and post-test. Results and Discussion; activity counseling attended by 18 senior executives and results obtained.